2013
DOI: 10.12944/crnfsj.1.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrition Education on Nutrition Knowledge and Iron Status in Primary School Pupils of Gatanga District, Muranga Country, Kenya

Abstract: School-age children are both growing and learning, and anaemia can affect cognitive function, motor performance and educational achievements of this age group. Nutrition education has not been given the priority it deserves in primary schools due to the busy school curriculum. It is in this light this study was designed for one teaching calendar year. Subjects & methods: Pupils (n=601) covering the age 11-18 years were included. The main objective of this study was to evaluate the effects of three main Nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
3
4
0
1
Order By: Relevance
“…Moreover, the mean hemoglobin of the studied children increased significantly after the nutritional educational sessions. These results were similar to the results presented by Gitau et al in Kenya (12.8 g/dl-13.4 g/dl) and Grover and Choudhary in India (8.55 g/dl-10.66 g/dl) [22], [23]. Another study conducted in India in 2019 showed that anemia cure rate was higher in children in the intervention group compared with the control group (55.7% vs. 41.4%) [24].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the mean hemoglobin of the studied children increased significantly after the nutritional educational sessions. These results were similar to the results presented by Gitau et al in Kenya (12.8 g/dl-13.4 g/dl) and Grover and Choudhary in India (8.55 g/dl-10.66 g/dl) [22], [23]. Another study conducted in India in 2019 showed that anemia cure rate was higher in children in the intervention group compared with the control group (55.7% vs. 41.4%) [24].…”
Section: Discussionsupporting
confidence: 92%
“…However, the mean score of knowledge in the control group showed some improvement after intervention. The results of previous studies are in line with our own, as we found that the nutrition education has a significant impact in improving knowledge (75)(76)(77)(78) . In addition, these studies reported a significant difference in the mean scores between two groups (intervention and control) after intervention only, whereas no significant mean difference was observed at the baseline concurrent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…However, the proportion of improvement in knowledge and adherence was reported different between studies (83) . These differences are related to the duration of the intervention and the method(s) used to deliver the intervention (76) .…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de la baja aportación del atributo: « sexo en que predominan los TCA », a la calificación global: correlación ítem/total en los cuestionarios inicial y final de 0,156 y 0,150 respectivamente; se decidió mantenerlo en el cuestionario definitivo por el importante papel del sexo en todos los procesos relacionados con la alimentación y en particular con los TCA8, 11, 22. La diferencia entre grupos hallada en las calificaciones globales respecto al sexo, coincide con los resultados de otras investigaciones en que son las mujeres quienes demuestran un mayor nivel de conocimientos en nutrición o en alimentación y que suelen demostrar mayor predisposición a participar en estudios relacionados con la salud27, 28.…”
Section: Discussionunclassified